Etude De L’exposition Des Banques Islamiques Au Taux D’intérêts Et De L’implication Sur La Gestion Actif-Passif - Aaminou, Mohamed Wail; Moutahaddib, Aziz (European Scientific Journal, ESJ, 2017)
Theoretically, Islamic banks should not be exposed to the risk of interest rate fluctuations. Indeed, in the literature, Islamic finance is considered a finance without interest that stands out from conventional finance by means of profit sharing and losses. In practice, although Islamic banking products are not directly based on interest, several studies mentioned in this article have shown that these banks are not completely immune to this kind of risk. Moreover, unlike conventional banks, Islamic banks do not have the same flexibility to cover this risk since they do not use interest. So, the assessment of the level of exposure to interest risks and understanding its determinants is essential for studying the appropriate hedging strategies and the guarantee of stability of Islamic banks.